"We Are": The Fundamental Life Position. (April 2016) - Tudor, Keith
This article argues that the existential statement "We are" most accurately describes the fundamental life position of human beings and identifies some ontological, epistemological, methodological, and practical implications of this. Taking the phrase "I'm OK, You're OK" and its variants as its theme, the article critically examines the three elements of this central aspect of transactional analysis theory and philosophy, that is, in terms of the person, OKness, and existential life positions. In doing so, it offers some clarification regarding Klein's influence on Berne and some variations that are informed by and advance we psychology .